Systemic Inequalities in Higher Education Exit Exams: A Systematic Literature Review - Teshome, Samson Worku (EDUMALSYS Journal of Research in Education Management, 2025)
Exit exams in higher education are commonly utilized as tools for quality assurance; however, their implications for systemic inequalities remain inadequately examined. This systematic literature review investigates the extent to which exit exams contribute to or alleviate disparities related to socioeconomic status, race, and institutional resources. Applying the PRISMA framework, the review analyzes 32 peer-reviewed studies from varied national contexts, including Ethiopia, India, the United States, and Germany. The findings indicate that exit exams disproportionately disadvantage marginalized student populations due to structural inequities in exam design, unequal access to preparatory resources, and disparities in institutional support. In Ethiopia, for instance, rural students confront significant linguistic and infrastructural barriers, while African American students in the United States are often subject to culturally biased test content. These examinations have been found to exacerbate dropout rates, constrain curricular breadth, and introduce substantial financial burdens—particularly for students from low-income backgrounds. The review highlights the need for policy reform focused on inclusive assessment strategies, equitable educational support systems, and pedagogical frameworks that address diverse learner needs. It emphasizes that fair assessment practices are critical for advancing educational equity and social justice within higher education systems. Future research should further explore issues such as digital accessibility, longitudinal impacts on career trajectories, and alternative models of student evaluation that prioritize fairness and inclusivity.